Tindak Tutur Komisif dalam Debat Pilkada Jakarta Tahun 2024 - Fitria Ika Farizha (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to explore and analyze the forms of commissive speech acts that emerge in the Jakarta Gubernatorial Election debate, as well as their impact on voter perception. The approach used in this study is a descriptive qualitative approach. The data in this study are in the form of direct speech acts of commissive types in the delivery of vision and mission statements in the 2024 Jakarta Gubernatorial Election debate, which include commissive speech acts of promises and vows. The technique used in this study is documentary-based, with listening and note-taking techniques. The results of the data analysis concluded that the commissive speech acts in the delivery of the vision and mission in the 2024 Jakarta Gubernatorial Election debate included 9 utterances, consisting of 7 utterances of commissive speech acts of promises and 2 utterances of commissive speech acts of vows. The candidate pairs involved in the debate were Ridwan Kamil-Suswono, Dharma Pongrekun-Kun Wardana, and Pramono Anung-Rano Karno, each of whom used various forms of promises and commitments related to improving the quality of life for Jakarta's residents, infrastructure development, and economic growth.